Application of an Expert System with the Breadth First Search (BFS) Method in Diagnosing Areca Plant Diseases - Ferry Juliandri Pane; Eva Rianti; Hari Marfalino (Universitas Putra Indonesia YPTK Padang, 2024)
Current technological developments are growing very quickly and have produced a lot of software or systems that can make things easier for humans. Continuous scientific progress drives extensive technological development. One form of information technology known is an information system. One popular type of information system is an expert system, which can be used to improve various services. An expert system is a program that combines human knowledge into a computer to help solve problems that are usually solved by experts. This research aims to identify gaps in research that has been conducted, as well as encourage the development of new ideas and increase capabilities in utilizing existing research resources. Areca nut is a high agricultural resource so it has many benefits in the pharmaceutical industry. . The method that will be used in this research is Breadth First Search (BFS). The algorithm carries out the search process on all nodes that are at the same level or hierarchy one by one. An algorithm that performs a wide search that visits nodes in preorder, that is, visits a node first. There are 16 data on areca plant diseases here and have 33 symptoms which will be processed using the Breadth First Search Method. By diagnosing areca plant diseases using an expert system, it is hoped that we can find more in-depth information about diseases in areca palm trees.